2017
DOI: 10.1016/j.scitotenv.2016.09.204
|View full text |Cite
|
Sign up to set email alerts
|

Dietary predictors of urinary cadmium among pregnant women and children

Abstract: Background Cadmium is a toxic metal with modifiable exposure sources including diet. In pregnant women and children, unique dietary habits may contribute to DCd, and the relationship of diet to overall cadmium exposure can depend on specific factors during these transitional time periods. Objectives This study aimed to identify and quantify food sources of DCd, describe the distribution of UCd, and determine the relationship of DCd and intake of specific foods with UCd, stratified by maternal smoking history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 39 publications
(62 reference statements)
2
19
0
Order By: Relevance
“…Maternal lead exposure was correlated with prenatal cadmium exposure ( r = 0.17, p = 0.028) and previous studies in this cohort demonstrate relationships of prenatal lead with childhood growth (26, 33, 38). Maternal fruit and vegetable intake was positively associated with urinary cadmium in pregnant women in our population, as previously published (25) and literature suggests that maternal diet is related to anthropometry in childhood (39).…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Maternal lead exposure was correlated with prenatal cadmium exposure ( r = 0.17, p = 0.028) and previous studies in this cohort demonstrate relationships of prenatal lead with childhood growth (26, 33, 38). Maternal fruit and vegetable intake was positively associated with urinary cadmium in pregnant women in our population, as previously published (25) and literature suggests that maternal diet is related to anthropometry in childhood (39).…”
Section: Methodssupporting
confidence: 86%
“…The study population and methods for measuring cadmium exposure and anthropometric outcomes have been described in detail elsewhere (25, 26). Briefly, our study population consists of participants from the Early Life Exposure in Mexico to Environmental Toxicants (ELEMENT) project, wherein three sequentially enrolled cohorts of pregnant women were recruited between 1997 and 2004 from maternity hospitals in Mexico City serving low- to moderate-income populations.…”
Section: Methodsmentioning
confidence: 99%
“…The median specific-gravity-adjusted urinary cadmium concentration was 0.06 μg/L (5%, 95%: 0.02, 0.17 μg/L). This is similar to levels reported for U.S. school children participating in the 1999-2004 NHANES (median 0.078 for 6-7 y-olds (Ciesielski et al, 2012), higher than in Danish children (median 0.021 μg/L), but lower than in children from several European countries (median ranges 0.14 -0.38 μg/L) (Aguilera et al, 2010;Exley et al, 2015;Fucic et al, 2015;Molina-Villalba et al, 2015;Protano et al, 2016;Roca et al, 2016) or Mexico (median 0.14 μg/L) (Moynihan et al, 2017) and especially lower than in children with rice-based diets, for example, 0.30 μg/L in 5 year-old rural Bangladeshi children (Kippler et al, 2010). We found no difference in urinary cadmium between girls and boys.…”
Section: Discussionmentioning
confidence: 72%
“…Among adults from Bangladesh, for example, the estimated daily intake of Cd from the diet was 35 µg/day, of which only 2% came from meats/fish, with much greater contributions from green vegetables (35%) and from steamed rice (54%) [20]. Similarly, among Mexican women, the contribution of meat and poultry to daily Cd consumption was low compared with the contribution of vegetables, grains, corn, and potatoes [23]. Among adults from northern Italy, whose average diet is about 8% meats, 10% vegetables, and 12% grains by weight, meat also contributed only a small amount (IQR 0.05-0.12 µg/day) to the estimated daily Cd exposure [58].…”
Section: Discussionmentioning
confidence: 99%
“…For example, among 50-79-year-old women participating in the US Women's Health Initiative, higher consumption of vegetables and grains was associated with higher dietary Cd exposure [22]. Among pregnant women from Mexico, the urinary Cd concentration measured during the third trimester was positively associated with estimated Cd in the diet but only among non-smokers [23]. A further study, however, found no associations between a range of food items and blood Cd concentrations (B-Cd) in premenopausal women in the USA [24].…”
Section: Introductionmentioning
confidence: 99%